FABRICATION OF CU MODIFIED NANO CHITOSAN WITH BROMOCRESOL GREEN AS INTELLIGENT PACKAGING - M Aras, Neny Rasnyanti; Irwana, Adinda; Utami, Ameliana (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
In recent advancements, the development of smart packaging systems for food has focused on utilizing composite materials to enhance functionality and sustainability. In this study, the composite film from chitosan and PVA was combined at various concentrations (ranging from 0.1% to 0.5%) with the addition of Cu(500mM) and 1% STPP at a 5:1 ratio. An additional indicator was included to detect fish spoilage. The synthesized chitosan material was then blended with PVA to form a composite film. The film was characterized using FTIR, which confirmed the presence of fingerprint vibrations indicating the cross-linking between TPP, chitosan, and Cu. These bonds were observed at wave numbers 1118 cm-1, 879 cm-1, and 603 cm-1. SEM analysis revealed that the film had particle sizes ranging from 865 nm to 1.49 μm. XRD analysis showed distinctive features of pure chitosan and chitosan composite. The composite film K-05 produced an amorphous structure, indicating decreased crystallinity due to the addition of STPP and Cu. The water uptake test demonstrated that an increased concentration of chitosan in the composite led to higher absorption and solubility effects. Conversely, the addition of chitosan in the film decreased water vapor permeability as determined by the water vapor permeability test. The antibacterial test conducted on all films (concentration of 0.1% to 0.5%) indicated that the films K-01 and K-02 exhibited the best zone of inhibition against Escherichia coli. This study sucessfully synthesized and characterized a smart packaging film composed of polyvinyl alcohol (PVA), chitosan, copper (Cu), and bromocresol green (BCG) indicator, designed to monitor food freshness through visual pH changes and inhibition of microbial growth.